2019
DOI: 10.1177/1753466619841350
|View full text |Cite
|
Sign up to set email alerts
|

Omalizumab and long-term quality of life outcomes in patients with moderate-to-severe allergic asthma: a systematic review

Abstract: Background: Asthma is a highly prevalent chronic inflammatory airways disease, with a considerable impact on quality of life (QoL). To express the effects of asthma on patients’ subjective experience, patient-reported outcomes (PROs) represent an important instrument. The asthma QoL questionnaire (AQLQ) is one of the main PROs among these. Materials and methods: To identify long-term asthma-related QoL outcomes associated with omalizumab therapy in patients with moderat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 49 publications
1
7
0
1
Order By: Relevance
“…Aligned with our results, previous SR of benralizumab, dupilumab, mepolizumab, omalizumab and reslizumab in severe asthma reported a reduction to approximately half of exacerbations, and an improvement in health‐related QoL scores, asthma control and FEV 1 . However, there are some important differences that need to be mentioned.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Aligned with our results, previous SR of benralizumab, dupilumab, mepolizumab, omalizumab and reslizumab in severe asthma reported a reduction to approximately half of exacerbations, and an improvement in health‐related QoL scores, asthma control and FEV 1 . However, there are some important differences that need to be mentioned.…”
Section: Discussionsupporting
confidence: 88%
“…Aligned with our results, previous SR of benralizumab, dupilumab, mepolizumab, omalizumab and reslizumab in severe asthma reported a reduction to approximately half of exacerbations, and an improvement in health-related QoL scores, asthma control and FEV 1 . [61][62][63][64][65][66][67][68] However, there are some important differences that need to be mentioned. Previous mepolizumab SR allowed the inclusion of nonapproved doses, 64,65 while the current SR included only licensed doses and routes of administration making the results more applicable to the daily practice.…”
Section: Current Results In the Context Of Previous Resultsmentioning
confidence: 99%
“…However, previous studies have shown strong evidence that omalizumab can provide long-term efficacy in management of allergic asthma. 42 , 43 …”
Section: Discussionmentioning
confidence: 99%
“…[20][21][22][23] Omalizumab reduces the frequency of clinically significant asthma exacerbations and the requirement for inhaled corticosteroids while improving asthma symptoms, lung function, and asthma-related quality of life. 20,[24][25][26][27] Omalizumab has also been shown to have a favorable safety profile and is well tolerated. 28 Two prospective, randomized, US-based clinical trials evaluating pediatric and adolescent patients with allergic asthma have shown the efficacy of omalizumab in decreasing exacerbations in inner-city populations, which are represented by greater than 90% Black or Hispanic race or ethnicity.…”
Section: Introductionmentioning
confidence: 99%